Predictive HR Analytics: Forecasting Workforce Needs with AI and Big Data - Nishitha Reddy Nalla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The rapid advancements in artificial intelligence (AI) and big data analytics are transforming human resource (HR) management. Predictive HR analytics enables organizations to anticipate workforce needs, optimize talent management, and enhance employee engagement. This paper explores the role of AI and big data in forecasting workforce trends, discusses various analytical models used in HR, and highlights real-world applications. Furthermore, it examines challenges, ethical considerations, and future research directions in predictive HR analytics.